Efeito da idade sobre as principais características andrológicas de touros Brangus-Ibagé criados extensivamente no estado do Mato Grosso do Sul - Brasil - Oliveira, Letícia Zoccolaro [UNESP]; Oliveira, Clara Slade [UNESP]; Monteiro, Fabio Morato [UNESP]; de Lima, Vera Fernanda Martins Hossepian [UNESP]; de Lima, Fernando Martins; Costa, Marcelo Zoccolaro (My University, 2011)
Background: Bull fertility is extremely important for beef cattle production systems and has a multiplier impact on the economical and zootechnical indexes of the herd. Bulls raised in tropical conditions may present varied seminal characteristics due to, among other causes, different management practices and quality of pastures. Another factor that influences the semen characteristics is the age of the sire. The reproductive potential of bull evaluated through the andrological exam aims to ensure the semen quality and to improve the herd reproductive efficiency. The aim of this study was to evaluate the main semen parameters of Brangus-Ibagé bulls extensively reared in eastern Mato Grosso do Sul state and to verify the effect of age on the andrological characteristics analyzed. It was also evaluated the correlation between age, scrotal circumference, and physical and morphological sperm characteristics produced by the Brangus bulls. Materials, Methods & Results: The study took place in the month of July 2010, during the routine andrological examination of 168 synthetic Brangus-Ibagé bulls (5/8 Angus x 3/8 Nelore), belonging to the same property. For data analysis the animals were divided by age groups: animals younger than 4 years (Age I), animals between 4 and 8 years of age (Age II), and animals between 8 and 15 years of age (Age III). In another analysis, the animals were grouped according to the sperm motility pattern obtained from the semen collection: sperm motility lower than 40% (Motility I), sperm motility between 40 and 70% (Motility II) and sperm motility between 70 and 90% (Motility III). The results of the present study demonstrated an effect of age (P <0.05) on the following androgical characteristics: scrotal circumference, ejaculate volume, sperm vigor, major defects, minor defects and total defects. It was also observed that the animals with higher sperm motility presented higher (P <0.05) scrotal circumference, and lower (P <0.05) percentages of major and total defects. Among the andrological characteristics evaluated in the present work, it was observed positive correlations between age and scrotal circumference (R =0.299; P =0.000), age and volume of ejaculate (R =0.161; P =0.037), age and major defects (R =0.188; P =0.015), sperm motility and scrotal circumference (R =0.245; P =0.001), sperm motility and sperm vigor (R =0.483; P =0.000), and between major defects and total defects (R =0.946; P =0.000). Also, negative correlations were observed between sperm motility and total defects (R =-0.372; P =0.000), sperm vigor and major defects (R =-0.498; P =0.000), and sperm vigor and total defects (R =-0.432; P =0.000). Discussion: Based on the results of this study it was concluded that the Brangus-Ibagé bulls utilized for natural breeding in eastern Mato Grosso do Sul, Brazil, presented satisfactory semen quality taking into account the quality of the pastures where the animals were located. In addition, the scrotal circumference, the ejaculate volume, the sperm vigor, and the percentage of morphological characteristics were influenced by the age of the bulls. Therefore, considering the production system and the environmental conditions, the animals with age between 4 and 8 years were superior regarding the sperm parameters evaluated.
Effect of age on the andrological characteristics of Brangus-Ibagé bulls extensively reared in Mato Grosso do Sul State - Brazil
Keywords: Age; Brangus; Semen characteristics; Sperm morphology